In Vitro Gap Changes After Porcelain Firing Cycles of Three and Four Unit of CAD/CAM Milling, Laser Sintering and Cast Metal Ceramic Restorations - TÜRKER, ŞEBNEM BEGÜM (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objectives: Marginal adaptation changes during the veneering process is an important factor in the clinical success of metal framework techniques such as conventional cast metal cores (LW), CAD-CAM Metal Milling (MM) and Direct Metal Laser Sintering (DMLS). The aim of this study is to evaluate the marginal fit changes between three- and four-unit's metal ceramic fixed partial dentures (FPD's) fabricated by Lost Wax (LW), CAM Metal Milling (MM) and (Direct Metal Laser Sintering) DMLS metal framework techniques after porcelain firing cycles (PFC). Methods: A total of 60 stainless steel three and four unit FPD's models were fabricated. Specimens were randomly divided into three groups to fabricate metal ceramic FPD's frameworks with LW, MM and DMLS techniques. Before and after PFC, cross-sections from silicone replicas were obtained, sectioned, examined and measured with a light microscope. The statistical analysis was done with Mann-Whitney U and Kruskal Wallis and Wilcoxon Signed Ranks tests. Results were evaluated at 95% of confidence interval and p<0.05 level. Results: There was a statistically significant difference between the three and four unit of FPD's, before PFC for LW and MM (p:0.000) and DMLS (p:0.019)'s groups and only DMLS (p:0.006)'s group was statistically significant after PFC. The mean marginal gaps of LW technique was higher than the MM and DMLS's techniques before PFC. After PFC, DMLS's technique results were higher than LW and MM technique but, no statistically significant difference was found between the marginal gap values of the three and neither for four units of DMLS's FPD's. Conclusion: PFC decreases the mean marginal gap of the LW and MM group, but, there was a slight increase for DMLS group. However, all the marginal gap values obtained were in clinical acceptance level for three and four-units FPD's for all tested specimens.
Keywords: Marginal gap; lost wax; CAD/CAM; laser sintering; porcelain firing cycle; FIXED DENTAL PROSTHESES; MARGINAL FIT; INTERNAL FIT; CLINICAL-EVALUATION; CROWNS; COPINGS; DISCREPANCIES; DISTORTION; ZIRCONIUM; ACCURACY